2016
DOI: 10.1016/j.ijid.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the rapid influenza detection tests GOLD SIGN FLU and Quick Navi-Flu for the detection of influenza A and B virus antigens in adults during the influenza season

Abstract: As the characteristics and accuracy of rapid influenza detection tests (RIDTs) vary, the development of a high-performance RIDT has been eagerly anticipated. In this study, the new RIDT GOLD SIGN FLU and the existing RIDT Quick Navi-Flu were evaluated in terms of detecting the antigens of influenza viruses A and B in Japanese adults with influenza-like symptoms. The study was performed from December 2013 to March 2014. Among the 123 patients from whom nasopharyngeal swab specimens were collected, 59 tested pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
(20 reference statements)
0
16
1
Order By: Relevance
“…To our knowledge, no previous study has focused on the timing of visits to healthcare facilities by ILI patients. Akaishi and colleagues [16] suggested that the median time between onset of influenzalike symptoms and visiting hospitals in Japan was 26.2 h. Fowlkes and colleagues, however, reported that 36.0% of medically-attended influenza cases had visited healthcare facilities more than 2 days after symptom onset [17]. It is difficult to compare these two results directly, but 26.2 h (about 1 day) from symptom onset seems very early.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no previous study has focused on the timing of visits to healthcare facilities by ILI patients. Akaishi and colleagues [16] suggested that the median time between onset of influenzalike symptoms and visiting hospitals in Japan was 26.2 h. Fowlkes and colleagues, however, reported that 36.0% of medically-attended influenza cases had visited healthcare facilities more than 2 days after symptom onset [17]. It is difficult to compare these two results directly, but 26.2 h (about 1 day) from symptom onset seems very early.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the recommendation of the Infectious Disease Society of America [18], Japanese physicians usually use RIDT, rather than a molecular assay such as reversetranscription polymerase chain reaction (RT-PCR). This may be because the rapid test has extremely high sensitivity and specificity in the early phases of symptoms [16,[19][20][21] and most patients in Japan visit physicians in these early stages, making the rapid test more appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the available number of RADTs for hMPV is low because hMPV was first identified in 2001 13 . RADTs can be used in point-of-care (POC) settings, but they are less sensitive than molecular diagnostic tests such as PCR and other nucleic acid amplification tests (NAATs) 14,15 . More recently, highly sensitive point-of-care testings (POCTs) based on NAAT that are easy to use in clinical settings have been developed.…”
mentioning
confidence: 99%
“…Contrary to the recommendation of the Infectious Disease Society of America [18], Japanese physicians usually use RIDT, rather than a molecular assay such as reverse-transcription polymerase chain reaction (RT-PCR). This may be because the rapid test has extremely high sensitivity and specificity in the early phases of symptoms [16,[19][20][21] and most patients in Japan visit physicians in these early stages, making the rapid test more appropriate.…”
Section: Introductionmentioning
confidence: 99%